Procedures of the Ministry of Interior in organizing the 1997 Jordanian Parliamentary elections - Adil Abdul Qadir, Layla (Journal of College of Education, 2022)
The Jordanian atmosphere for the conduct of engineering, The parliamentary elections after the Jordanian government is ten-months before the end of its term, and the atmosphere by the Ministry of Interior was clear, including the modern and advanced introduction of services and works in all departments of the state to be ready with its agencies during a sufficient period Abstract from the occasions. According to the ministry’s directives, the Ministry of Information has equipped a special media center for the parliamentary elections, which provides local and international journalists with direct coverage in all polling and counting centers in the Kingdom, as well as concluding an agreement with Japan to provide decision-makers with accurate information in addition to providing services and information to voters and allocating funds for this purpose. The Jordanian government insisted on The statement of the Prime Minister, Abd al-Salam al-Majali, is its refusal for international observers to supervise the elections, which raises doubt about the main reason behind their refusal. To provide all appropriate conditions for the conduct of the election mechanism.